Speech Prosody 2014 2014
DOI: 10.21437/speechprosody.2014-196
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical stress generation with Fujisaki model in expressive speech synthesis

Abstract: This article presents preliminary results indicating that speakers have a different pitch range when they speak a foreign language compared to the pitch variation that occurs when they speak their native language. To this end, a learner corpus with French and German speakers was analyzed. Results suggest that speakers indeed produce a smaller pitch range in the respective L2. This is true for both groups of native speakers. A possible explanation for this finding is that speakers are less confident in their pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…Speech Analyses Because origin (e.g., Ordin & Mennen, 2017;Zimmerer et al, 2014) and language (e.g., Andreeva et al, 2014;Keating & Kuo, 2012;Traunmüller & Eriksson, 1995) influence speech characteristics and vocal quality parameters, we only analyzed participants who were native French speakers with European ascendants. We also only focused on participants who declared themselves as homosexual and heterosexual (we excluded those who declared to be bisexual or other).…”
Section: Speech Samples and Acoustic Analysis Proceduresmentioning
confidence: 99%
“…Speech Analyses Because origin (e.g., Ordin & Mennen, 2017;Zimmerer et al, 2014) and language (e.g., Andreeva et al, 2014;Keating & Kuo, 2012;Traunmüller & Eriksson, 1995) influence speech characteristics and vocal quality parameters, we only analyzed participants who were native French speakers with European ascendants. We also only focused on participants who declared themselves as homosexual and heterosexual (we excluded those who declared to be bisexual or other).…”
Section: Speech Samples and Acoustic Analysis Proceduresmentioning
confidence: 99%
“…In read speech, BrE and IndE hardly differ in pitch dynamism as measured by PDQ. Both have higher PDQ scores than French and German speakers [11]. By contrast, in spontaneous speech, PDQ is higher for IndE than for BrE, indicating a wider pitch range.…”
Section: Dicussionmentioning
confidence: 76%
“…Such attitudinal evaluations may be acutely felt by language learners, who, as a range of studies has shown, tend to have a compressed pitch range compared to native speakers [3,[10][11][12]. This result has also been confirmed for speakers learning English as a foreign language, such as L1 Swedish or L1 Italian learners of English, who use English mainly for international communication [13,14].…”
Section: Introductionmentioning
confidence: 94%
“…As final rises (H%) are used in French and German to signal interrogativity, German learners might tend to generalize the H% pattern (and the marker ECQ) for all types of questions -in spite of the pragmatic differences between and the alluded intonational variability in both languages (see studies on interrogatives and their prosody in L2: [21], [22], [23] Earlier research on L2 intonation has shown that learner data are characterized by a narrower pitch range and a lower degree of F0 variability (see [24] for L2 French read data produced by German learners). The same holds true for speech rate: L2 speech is known to be typically slower than L1 speech ( [25]).…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…SD/mean), based on manually corrected files (exclusion of octave jumps and wrong measurements). In accordance with the method applied by [24], we used time steps of 0.01s for male and of 0.005s for female subjects. We furthermore determined the speech rate (in syllables per second) for each utterance.…”
Section: Parameters Analyzedmentioning
confidence: 99%